The suitability of sputum and blood culture in children with pneumonia at Sanglah General Hospital, Bali, Indonesia - Ayu Setyorini Mestika Mayangsari; Ida Bagus Subanada; Putu Siadi Purniti; Wayan Agustini Selumbung (Intisari Sains Medis, 2019)
Background: Pneumonia is one of the diseases in children with high morbidity, especially in children under 5 years old. In developing countries, the most common cause of pneumonia is bacteria. There is a newer method that gives a better reflection of the aetiology, which is the sputum examination. This study aims to determine the suitability of sputum and blood culture in children with pneumonia at Sanglah General Hospital, Bali.Methods: A cross-sectional study was conducted at Respirology Subdivision in Department of Child Health Sanglah Hospital from November 2016 until February 2017. A categorical comparative matching was carried out between 2 formula groups. The sputum culture and blood culture were obtained through Microbiology Laboratory at Sanglah General Hospital. Data were analysed using SPSS version 16 for Windows.Results: There were 50 children with pneumonia enrolled in this study. The children aged less than 1 years old were predominant (62%). There were a statistically systematic difference and only a fair agreement between blood and sputum culture (Ä¸=0.257; p= 0.004). In a subject with positive sputum culture, 90.9% had a better outcome than the positive blood culture even though no statistically significant (RR=0.23; 95%CI: 0.15-22.53)Conclusion: There is suitability between the culture of sputum and blood cultures in children with pneumonia. Sputum culture has a higher probability to reveal the microorganism compared to blood cultures.